2020
DOI: 10.3390/w12102796
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Analytics and Its Role to Support Groundwater Management in the Southern African Development Community

Abstract: Big data analytics (BDA) is a novel concept focusing on leveraging large volumes of heterogeneous data through advanced analytics to drive information discovery. This paper aims to highlight the potential role BDA can play to improve groundwater management in the Southern African Development Community (SADC) region in Africa. Through a review of the literature, this paper defines the concepts of big data, big data sources in groundwater, big data analytics, big data platforms and framework and how they can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…On a conceptual level, the usefulness of a big data analytics platform for groundwater management has been recognized by the Southern African Development Community [23].…”
Section: Related Workmentioning
confidence: 99%
“…On a conceptual level, the usefulness of a big data analytics platform for groundwater management has been recognized by the Southern African Development Community [23].…”
Section: Related Workmentioning
confidence: 99%
“…India Water Tool version 2 (IWT 2.0) developed by Shiao et al (2015), provides high-resolution, user-friendly, and publicly available water platform to help companies, government agencies, and other users identify their water risks and prioritize their water management actions in India, which also alike of the present study. Furthermore, several other studies has been done by various researchers at different places around the world and found the developed web-GIS based information system is more user-friendly, and also provides the spatio-temporal information regarding water (Horne 2015;Evans et al 2020;Gaffoor et al 2020).…”
Section: Development Of Web Gis Based Water Resource Information Systemmentioning
confidence: 99%
“…Community members are aware of the benefits of big data-driven innovation in enhancing environmental performance, so they can exert pressure on companies to apply this technology for sustainability purposes. Literature has pointed out that the community can develop coercion mechanisms to boost the application of big data analytics (Gaffoor et al, 2020;Bag et al, 2021b). For example, the vision of community members for digitalization can lead to achieving sustainable development goals.…”
Section: Introductionmentioning
confidence: 99%